Does Inclusion in a Smaller S&P Index Create Value? - Becker-Blease,John; Paul,Donna (Financial Review, 2010)
This study finds overall increases in equity value surrounding addition to the S&P SmallCap and MidCap indexes from 1996 to 2003 and investigates sources of the value gains. Following addition, there are significant increases in proxy variables for stock liquidity and investor recognition, and changes in these variables are impounded into the permanent component of announcement share price revisions. We also find that changes in capital investment intensity are increasing in changes in stock liquidity, consistent with a reduction in the cost of capital following index addition.
Keywords: Finance